Development of a model for technology strategy elaboration - Mazlomi, Aliakbar; Mohd Yusuff, Rosnah (Engg Journals Publications, 2011)
Considering the role of industry in the economy, especially the developed countries and countries with automobile (automotive industry) seems to be necessary to develop technology development strategy. In this paper a model by choosing appropriate technology development strategy to how good we are. (So review existing models and evaluate their strengths and weaknesses of the measure applied in the industry with the closest model industry conditions is consistent with the practices were selected and other factors as the failure of this model was determined it developed a new model for strategy is presented).